2018
DOI: 10.1007/s42000-018-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal SSRI medications and offspring hippocampal plasticity: interaction with maternal stress and sex

Abstract: There is growing use of selective serotonin reuptake inhibitor antidepressant (SSRI) medications during the perinatal period to treat maternal affective disorders. Perinatal SSRI exposure can have a long-term impact on offspring neuroplasticity and behavioral development that remains to be fully elucidated. This mini-review will summarize what is known about the effects of perinatal SSRIs on plasticity in the developing hippocampus, taking into account the role that maternal stress and depression may have. Eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 89 publications
0
13
0
1
Order By: Relevance
“…However, several studies did find alterations in the brain as a result of perinatal SSRI exposure or maternal stress. To name a few, alterations were found in offspring's hippocampal 5-HT levels, it's metabolite 5-hydroxyindolacetic acid, the serotonergic transmission, the serotonin transporter gene expression and the 5-HT turnover (reviewed in [78]). Outside the serotonergic system, also long-term hippocampal plasticity effects of perinatal SSRIs have been reported, including changes in the expression of the brain-derived neurotrophic factor (BDNF [53];) and the epigenetic regulation of the BDNF gene [44,56].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies did find alterations in the brain as a result of perinatal SSRI exposure or maternal stress. To name a few, alterations were found in offspring's hippocampal 5-HT levels, it's metabolite 5-hydroxyindolacetic acid, the serotonergic transmission, the serotonin transporter gene expression and the 5-HT turnover (reviewed in [78]). Outside the serotonergic system, also long-term hippocampal plasticity effects of perinatal SSRIs have been reported, including changes in the expression of the brain-derived neurotrophic factor (BDNF [53];) and the epigenetic regulation of the BDNF gene [44,56].…”
Section: Limitationsmentioning
confidence: 99%
“…More hippocampal effects have been reported (e.g. for review, see [78]), and several other brain areas may play a role in the alterations found in the behavioral outcomes of the offspring as well. Similar alterations could have occurred in the offspring exposed to fluoxetine and/or maternal adversity in the rats described in the current study but this assumption is speculative, and the study of underlying mechanisms was beyond the scope of this study.…”
Section: Limitationsmentioning
confidence: 99%
“…It is, however, also able to alter developmental mechanisms and behaviors without counteracting prenatal stress; similar to the human study of Rotem-Kohave et al [145]. That both gestational SSRI exposure and prenatal stress can influence brain development independent of each other is also highlighted in another review focusing specifically on hippocampal plasticity [203].…”
Section: Maternal Ssri Intake Affects Animal Offspring 5-ht Signalingmentioning
confidence: 63%
“…That perinatal SSRI exposure, irrespective of prenatal stress, can impact the HPA-axis has been shown in other studies as well. Perinatal fluoxetine resulted in increased serum corticosteroid binding globulin, decreased hippocampal synaptic protein (PSD-95), reduced glucocorticoid receptor density in the hippocampus, and reduced glucocorticoid receptor density in the mPFC [150,160,203,237].…”
Section: Maternal Ssri Intake Affects Animal Offspring's Brain Circuimentioning
confidence: 99%
“…Neuroanatomical and functional connections among these structures determine the integration of nociceptive and affective signals and the involvement of the descending serotonergic system that regulates nociceptive signals in pain and depressive behaviors (Chaouloff, 2000). Since 5-HT1AR is involved in nociception (Granados-Soto et al, 2010) and psycho-emotional behavior (Savitz et al, 2009), changes in its activity in the prenatal period may manifest itself later in alteration of various types of adaptive behaviors (Knaepen et al, 2013, 2014; Kiryanova et al, 2017, 2018; Pawluski and Gemmel, 2018).…”
Section: Introductionmentioning
confidence: 99%